2012
DOI: 10.1099/vir.0.045427-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of heterosubtypic immunity between avian influenza subtypes H3N8 and H4N6 in multiple avian host species

Abstract: Low-pathogenicity avian influenza virus (LPAIV) can lead to epizootics that cause economic losses in poultry or the emergence of human-infectious strains. LPAIVs experience a complex immunity landscape as they are endemic in numerous host species, and many antigenically distinct strains cocirculate. Prevention and control of emergence of detrimental strains requires an understanding of infection/transmission characteristics of the various subtypes in different hosts, including interactions between subtypes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Our findings are in agreement with previous experimental studies that reported partial cross-protective immunity conferred by primary H3N8 inoculation against H4N6 virus challenge in mallards [20]. Our data also support results from a longitudinal field study where re-infections with phylogenetically related HA subtypes were rare in mallards, and cross-protection between subtypes within the H1 and H3 clades lasted for at least 30 days [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in agreement with previous experimental studies that reported partial cross-protective immunity conferred by primary H3N8 inoculation against H4N6 virus challenge in mallards [20]. Our data also support results from a longitudinal field study where re-infections with phylogenetically related HA subtypes were rare in mallards, and cross-protection between subtypes within the H1 and H3 clades lasted for at least 30 days [21].…”
Section: Discussionsupporting
confidence: 92%
“…Seasonal patterns of IAV prevalence among wild birds have been described; however, factors and mechanisms that drive diversity and prevalence of IAV subtypes such as the effects of homo- and heterosubtypic immunity remain unclear [14, 15]. Previous studies have demonstrated the induction of homosubtypic and partial heterosubtypic immunity in mallards [1620], and this has been supported further by field observations [21]. At the same time, additional studies are needed to understand better the effect of reinfections with common and less frequently detected subtypes of LPAIV on the ecology of influenza in the wild bird reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study clearly showed individual heterogeneity in shedding responses within hosts, similar to what has been observed previously in other species [8]. In addition, the infected mallard in the high-density stack only shed virus for a short duration and aside from a single day, only by the oral route.…”
Section: Discussionsupporting
confidence: 60%
“…B 281: 20140098 strain (homosubtypic immunity) [40,41]. In addition, the development of partial protection against other strains, defined as heterosubtypic or cross-protective immunity, may also occur [40,[42][43][44][45]. This seems to be true for sentinel mallards in nature [46].…”
Section: (B) What Is Governing the Seasonal Trends In Influenzamentioning
confidence: 99%